Mesostructural Design and Manufacturing of Open-Pore Metal Foams by Investment Casting - Alexander Martin Matz; Bettina Stefanie Mocker; Daniel Wyn Müller; Norbert Jost; Gunther Eggeler (Advances in Materials Science and Engineering)
The present paper describes the manufacturing process of open-pore metal foams by investment casting and the mesostructural/morphological evolution resulting from a new technique of modifying the precursor. By this technique, the precursor is coated with a polymer layer whereby a thickening of the struts occurs. Relative densities in the range of 1.85≤ρrel≤25% of open-pore metal foams can be achieved with high accuracy. The samples investigated have pore densities of ρP=7 ppi, 10 ppi, and 13 ppi. The relevant processing parameters needed for a homogenous formation of the polymer layer are determined for two different coating materials and the resulting open-pore foam’s mesostructure is characterized qualitatively and quantitatively. The alloy used for investment casting open-pore metal foamsis AlZn11. The microstructural evolution of these foams is evaluated as a function of the mesostructure. Differences in the microstructure are observed for foams with low and high relative densities and discussed in terms of cooling subsequent to investment casting.